Sistema para a Predição do Crescimento da Cortiça - Almeida, Alice; Tomé, Margarida (Silva Lusitana, 2008)
. Cork growth modelling was based on two models: cork growth model for complete rings and a model for total cork thickness prediction. The cork growth model was developed using data from 189 cork samples taken at breast height. Four biological growth functions were considered using their formulation as difference equations. The evaluation of the fitting and predictive ability of the models was based on model efficiency and on several statistics computed with the press residuals, complemented with graphical analysis to assess the regression assumptions. The model selected - Lundqvist-A - can be used to predict cork thickness in complete rings at any year of the cork rotation. The model for the prediction of total cork thickness is used to predict total cork thickness from the thickness in complete rings
The following values have no corresponding Zotero field: publisher: scielopt
Keywords: accumulated cork thickness in complete rings; cork growth; growth models; prediction; total cork thickness prediction